If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1f + 3 = -4f Reorder the terms: 3 + -1f = -4f Solving 3 + -1f = -4f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '4f' to each side of the equation. 3 + -1f + 4f = -4f + 4f Combine like terms: -1f + 4f = 3f 3 + 3f = -4f + 4f Combine like terms: -4f + 4f = 0 3 + 3f = 0 Add '-3' to each side of the equation. 3 + -3 + 3f = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 3f = 0 + -3 3f = 0 + -3 Combine like terms: 0 + -3 = -3 3f = -3 Divide each side by '3'. f = -1 Simplifying f = -1
| 7*3x=6x+9 | | x+1/3+x-2/6=x+6/12 | | -6j-8=-8j | | 1/4d+3/4=6 | | x+6/3+x-2/6=2x-3/12 | | 27=2-5(9-x) | | 3(t+1)=9 | | 1/2h-16=5/8h | | 8h+(-15h)+(-5)=(-19) | | 9+2x=15-3x | | 7(9+2x)=15-3x | | 4(c+2)=16 | | 4x/(x+2)=2 | | -(x)-6/2=15 | | 2j-3j+19=2 | | -12+n=1 | | x+9=5(2x+8) | | 80.75/z5 | | 7(9+-2x)=-33-7x | | x^2-7=4x-11 | | 1/9x^2-1=-3/4 | | 7(9+-2x)=3(5x-2) | | 4x+(4-x)-5=2x+3 | | 2(24-y)+2y=48 | | z=11+3(x+y)findx | | 7(9+-2x)=9(5x-2) | | 7(9+-2x)=9(7-2x) | | 8(100-k)+10k=840 | | 7(9+-2x)=9(7x-2) | | 16x^2-11x+26=0 | | 9c-36= | | (x+y)dx+(x-y)dy=0 |